High-strength high-temperature-resistant alloy strip for hot-end component and preparation process thereof
By forming a metal bonding layer and thermal barrier coating of modified Al-Si slurry and modified CaO-ZrO2 composite slurry on the alloy belt, the contradiction between thermal conductivity and high temperature resistance is solved, and an alloy belt with high strength, good thermal conductivity and corrosion resistance is achieved.
Patent Information
- Application Number
- CN202411956050.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-04-25
AI Technical Summary
There is a contradiction between thermal conductivity and high temperature resistance in existing alloy tapes for thermal end components. Magnesium alloys have good thermal conductivity but poor mechanical strength, which limits its application range.
A high-strength high-temperature resistant alloy tape including an alloy tape, a metal bonding layer and a thermal barrier coating are used. The alloy tape consists of Al, Cr, Mo, Fe and Ni. The metal bonding layer and thermal barrier coating are formed by modifying Al-Si slurry and modified CaO-ZrO2 composite slurry to improve its thermal conductivity, mechanical properties and corrosion resistance.
The alloy belt has high strength, good thermal conductivity and corrosion resistance at high temperatures, extending its service life and reducing maintenance costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy materials, in particular to a high-strength and high-temperature-resistant alloy strip for hot end components and a preparation process thereof. Background Art
[0002] Alloy belt is a material synthesized from a variety of metals. It has high strength and hardness, making it widely used in machinery, construction and other industries. Alloy belt also has good wear resistance and corrosion resistance, allowing it to be used in harsh working environments.
[0003] Alloy strips for hot end components usually require good thermal conductivity and high temperature resistance, but there are often contradictions between these properties. For example, magnesium alloy has good thermal conductivity, but its mechanical strength is poor, which limits its scope of application.
[0004] Therefore, we propose a high-strength and high-temperature resistant alloy strip for hot end components and a preparation process thereof. Summary of the invention
[0005] The object of the present invention is to provide a high-strength and high-temperature-resistant alloy strip for hot end components and a preparation process thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A high-strength, high-temperature-resistant alloy strip for a hot end component, comprising an alloy strip, a metal bonding layer and a thermal barrier coating; The alloy strip includes the following mass components: Al (aluminum): 10.5-20.5%, Cr (chromium): 5.5-10.5%, Mo (molybdenum): 8.0-12.0%, Fe (iron): 14.5-20.5%, and the balance is Ni (nickel).
[0007] In the above technical solution, aluminum has good thermal conductivity, quickly transfers heat, effectively reduces the temperature of the device, and improves the stability of the system. Aluminum is also corrosion-resistant, improves the corrosion resistance of the alloy strip, and prolongs its life. Chromium is a strengthening element in the alloy, which can refine the grains and improve the strength and hardness of the alloy by forming a reinforcing phase. The carbide formed by chromium also has good wear resistance, which helps the alloy strip to withstand friction for a long time and reduce wear. Molybdenum can form a solid solution with other elements to improve the mechanical properties of the alloy. Molybdenum has high oxidation resistance, high melting point and excellent corrosion resistance, so that it can maintain good stability in high temperature and high corrosion environment, prolong the service life of the alloy strip and reduce maintenance costs. Iron forms a solid solution or compound through interaction with other elements, so that the internal structure of the alloy strip changes, improves its strength and hardness. The iron element in the alloy can refine the grains, help improve the toughness and ductility of the alloy, and maintain integrity when impacted. Nickel is an element that expands the austenite zone and does not form carbides, which means that adding nickel to the alloy can make the alloy obtain an austenite structure at room temperature and maintain the stability of austenite at high temperatures.
[0008] A preparation process of a high-strength high-temperature resistant alloy strip for a hot end component comprises the following steps: S1: Melting the alloy into a slab; S2: grinding and finishing the slab described in S1, hot rolling, bright annealing, and grinding and finishing again to obtain a semi-finished alloy strip; S3: cold rolling, annealing, cold rolling again, annealing, and then inspecting and trimming the semi-finished alloy strip in S2 to obtain a finished alloy strip; S4: ultrasonically clean and dry the finished alloy strip described in S3, spray modified Al-Si (aluminum-silicon) slurry on the surface of the finished alloy strip, solidify it to form a metal bonding layer, and then coat the surface of the metal bonding layer with modified CaO-ZrO2 (calcium oxide-zirconium dioxide) composite slurry, solidify it to form a thermal barrier coating, and obtain a high-strength and high-temperature resistant alloy strip.
[0009] Furthermore, the temperature of the smelting and forming in S1 is 1400-1600°C.
[0010] Further, the hot rolling temperature in S2 is 1100-1300°C; Bright annealing in S2 is carried out in a bright annealing furnace protected by pure hydrogen. The process conditions are: temperature 1100-1300℃, time 5-15min, hydrogen injection volume 35-55m 3 / h.
[0011] Furthermore, the process conditions of cold rolling in S3 are: temperature 400-600°C, time 0.5-1.5h; The annealing process conditions are: temperature 1100-1300°C, time 50-90min.
[0012] Further, the process conditions of ultrasonic cleaning in S4 are: frequency 20-40 Hz, time 0.5-1.5 h; The process conditions of spraying in S4 are: spray volume 5-15mL / min, nozzle pressure 2-10KPa; The curing process conditions in S4 are: temperature 900-1100°C, time 1-3h; The thickness of the metal bonding layer in S4 is 0.3-0.8 mm; The thickness of thermal barrier coating in S4 is 0.5-1mm.
[0013] Furthermore, the preparation process of the modified Al-Si slurry is as follows: Step 1: Mix nano-La2O3 with NaCl (sodium chloride) solution and perform ultrasonic treatment to obtain La2O3 slurry; Step 2: Mix Al (aluminum) powder, Si (silicon) powder, Al2O3 (aluminum oxide) powder and the La2O3 slurry in step 1, add a silane coupling agent, stir evenly, and obtain a modified Al-Si slurry.
[0014] Furthermore, in step 1, the NaCl solution is obtained by mixing NaCl, anhydrous ethanol, and deionized water in a mass ratio of (0.3-0.5): 1:1 and stirring evenly; In step 1, the mass ratio of nano-La2O3 and NaCl solution is (1-3): (5-8).
[0015] Furthermore, in step 2, the mass ratio of Al powder, Si powder, Al2O3 powder, La2O3 slurry and silane coupling agent is (1-2): (0.5-1): (4-6): (8-15): (0.05-0.1).
[0016] Furthermore, nano-La2O3: 200nm, purity 99%, sourced from Ganzhou Qiming New Materials Co., Ltd.; NaCl: CAS No. 7647-14-5, purity 98%, sourced from Laizhou Haimeng Salt Chemical Co., Ltd.; Anhydrous ethanol: CAS No. 64-17-5, purity 99%, from Jinan Rongchang Chemical Co., Ltd.; Al powder: 2000 mesh, purity 99.85%, from Hunan Jinhao New Materials Technology Co., Ltd.; Si powder: 1000 mesh, purity 99.99%, from Hebei Teng Bimetallic Materials Co., Ltd.; Al2O3 powder: CAS No. 1344-28-1, 8-12 μm, from Yangzhou Zhongtianli New Materials Co., Ltd. Silane coupling agent: KH560, purity 99%, from Shandong Yuanjin Materials.
[0017] In the above technical scheme, the Al-Si slurry is modified by using nano-La2O3, so that the heat resistance and aging resistance of the bonding layer are enhanced. The oxygen atoms in the nano-La2O3 and the silicon atoms in the Al-Si slurry form a tight chemical bond, which strengthens the interaction between molecules and improves the bonding strength of the bonding layer. Nano-La2O3 can also promote the dispersibility of the Al-Si slurry, help to form a dense and uniform structure, and further improve the wear resistance and impact resistance of the bonding layer. The aluminum and silicon elements in the Al-Si slurry have good chemical stability and strong corrosion resistance. At the same time, nano-La2O3 also has good corrosion resistance. The two work together to further enhance the corrosion resistance of the bonding layer.
[0018] Furthermore, the preparation process of the modified CaO-ZrO2 composite slurry is as follows: (1) C4H6CaO4 (calcium acetate), ZrOCl2·8H2O (zirconium oxychloride) and ethanol aqueous solution are mixed, polyethylene glycol is added, stirred evenly, the pH is adjusted to 9-11, stirred evenly, ultrasonically dispersed, and the obtained mixed solution is heated in a water bath to 50-70°C to form a gel, dried and ground, and calcined to obtain CaO-ZrO2 composite powder; (2) Mix the CaO-ZrO2 composite powder, nano-Al2O3 and anhydrous ethanol, disperse them by ultrasonication, add a silane coupling agent dropwise, heat and stir to react until it becomes viscous, and obtain a modified CaO-ZrO2 composite slurry.
[0019] Furthermore, the mass fraction of the ethanol aqueous solution in (1) is 80%.
[0020] Further, the molar ratio of C4H6CaO4 and ZrOCl2·8H2O in (1) is (1-3): (1-3); The mass ratio of C4H6CaO4, ethanol aqueous solution and polyethylene glycol is 1:(6-10):(0.05-0.1).
[0021] Furthermore, the drying time in (1) is 8-12 h at a temperature of 90-110°C; The calcination process conditions are: temperature 700-1100°C, time 2-4h.
[0022] Furthermore, in (2), the mass ratio of CaO-ZrO2 composite powder, nano-Al2O3, anhydrous ethanol, and silane coupling agent is (5-10): (0.5-1): (15-25): (0.05-0.1).
[0023] Furthermore, the process conditions for the heating and stirring reaction in (2) are: temperature 65-85°C, stirring speed 80-100 r / min.
[0024] Furthermore, the process conditions of ultrasonic dispersion are: frequency 20-40kHz, time 3-5min.
[0025] Further, C4H6CaO4: CAS number 5743-26-0, purity 98%, sourced from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd.; ZrOCl2·8H2O: CAS number is 13520-92-8, purity is 99%, from Langfang Qianyao Technology Co., Ltd. Polyethylene glycol: CAS number is 25322-68-3, from Nanjing Reagent; Nano Al2O3: 20-30nm, purity 00.00%, sourced from Beijing Dekedaojin Technology Co., Ltd.
[0026] In the above technical scheme, the CaO-ZrO2 composite powder is prepared by the auxiliary sol-gel method. The raw materials C4H6CaO4 and ZrOCl2·8H2O are first hydrolyzed and then gradually form sol particles through polycondensation reaction. After heating in a water bath, the sol particles further react to form a gel with a three-dimensional network structure, thereby achieving mutual adhesion between CaO and ZrO2 molecules and improving the stability of the composite powder. The CaO-ZrO2 composite powder is then modified by nano-Al2O3 coating, which, on the one hand, improves the surface morphology of the composite powder, making it more uniform and dense, and on the other hand, improves the dispersibility of the powder in the slurry, thereby improving the mechanical properties, wear resistance and high temperature resistance of the thermal barrier coating.
[0027] Compared with the prior art, the present invention has the following beneficial effects: 1. The Al-Si slurry is modified by nano-La2O3 to enhance the heat resistance and aging resistance of the bonding layer. The oxygen atoms in nano-La2O3 and the silicon atoms in the Al-Si slurry form a tight chemical bond, which strengthens the interaction between molecules and improves the bonding strength of the bonding layer. Nano-La2O3 can also promote the dispersibility of the Al-Si slurry, help to form a dense and uniform structure, and further improve the wear resistance and impact resistance of the bonding layer; the aluminum and silicon elements in the Al-Si slurry have good chemical stability and strong corrosion resistance. At the same time, nano-La2O3 also has good corrosion resistance. The two work together to further enhance the corrosion resistance of the bonding layer.
[0028] 2. CaO-ZrO2 composite powder was prepared using the auxiliary sol-gel method. The raw materials calcium acetate and zirconium oxychloride were first hydrolyzed and then gradually formed sol particles through condensation reaction. After heating in a water bath, the sol particles further reacted to form a gel with a three-dimensional network structure, which achieved mutual adhesion between CaO and ZrO2 molecules and improved the stability of the composite powder. The CaO-ZrO2 composite powder was then modified by nano-Al2O3 coating. On the one hand, the surface morphology of the composite powder was improved, making it more uniform and dense. On the other hand, the dispersion of the powder in the slurry was improved, thereby improving the mechanical properties, wear resistance and high temperature resistance of the thermal barrier coating.
[0029] 3. Curing at high temperature to form a metal bonding layer and a thermal barrier coating. The metal bonding layer undergoes a thermal corrosion reaction, in which Al is very easy to form an aluminum oxide film with good stability, which helps to protect the substrate from further corrosion. At high temperature, the metal bonding layer reacts with Fe, Ni, Cr and other elements in the alloy strip to form a stable compound, which adheres to the alloy strip and enhances the bonding strength between the alloy strip and the metal bonding layer. The Si in the metal bonding layer can reduce the thermal expansion coefficient of the thermal barrier coating surface and reduce the stress of zirconium oxide in the thermal barrier coating during use, so that it matches the thermal expansion coefficient of the metal bonding layer, thereby improving the bonding force between the thermal barrier coating and the metal bonding layer, further enhancing the bonding force between the alloy strip, the metal bonding layer and the thermal barrier coating, and improving the high temperature resistance, corrosion resistance and service life of the alloy strip. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] In the following specific implementations, Nano La2O3: 200nm, purity 99%, sourced from Ganzhou Qiming New Materials Co., Ltd. NaCl: CAS No. 7647-14-5, purity 98%, sourced from Laizhou Haimeng Salt Chemical Co., Ltd.; Anhydrous ethanol: CAS No. 64-17-5, purity 99%, from Jinan Rongchang Chemical Co., Ltd.; Al powder: 2000 mesh, purity 99.85%, from Hunan Jinhao New Materials Technology Co., Ltd.; Si powder: 1000 mesh, purity 99.99%, from Hebei Teng Bimetallic Materials Co., Ltd.; Al2O3 powder: CAS No. 1344-28-1, 8-12 μm, from Yangzhou Zhongtianli New Materials Co., Ltd. Silane coupling agent: KH560, purity 99%, from Shandong Yuanjin Materials; C4H6CaO4: CAS number is 5743-26-0, purity is 98%, from Tianjin Jinhui Taiya Chemical Reagent Co., Ltd.; ZrOCl2·8H2O: CAS number is 13520-92-8, purity is 99%, from Langfang Qianyao Technology Co., Ltd. Polyethylene glycol: CAS number is 25322-68-3, from Nanjing Reagent; Nano Al2O3: 20-30nm, purity 00.00%, from Beijing Dekedaojin Technology Co., Ltd.; Prepare NaCl solution: mix NaCl, anhydrous ethanol and deionized water in a mass ratio of (0.3-0.5):1:1, stir evenly to obtain NaCl solution.
[0032] Embodiment 1: A process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component, comprising the following steps: 1. Preparation of modified Al-Si slurry: Step 1: Mix nano-La2O3 and NaCl solution in a mass ratio of 1:5, and ultrasonicate to obtain La2O3 slurry; Step 2: Mix Al powder, Si powder, Al2O3 powder and the La2O3 slurry in step 1, add silane coupling agent, stir evenly, and obtain modified Al-Si slurry; in step 2, the mass ratio of Al powder, Si powder, Al2O3 powder, La2O3 slurry, and silane coupling agent is 1:0.5:4:8:0.05; 2. Preparation of modified CaO-ZrO2 composite slurry: (1) C4H6CaO4, ZrOCl2·8H2O and 80% ethanol aqueous solution were mixed, polyethylene glycol was added, stirred evenly, the pH was adjusted to 9, stirred evenly, ultrasonically dispersed, and the obtained mixed solution was heated to 50°C in a water bath to form a gel, dried and ground, and calcined to obtain CaO-ZrO2 composite powder; (2) CaO-ZrO2 composite powder, nano-Al2O3 and anhydrous ethanol were mixed, ultrasonically dispersed, silane coupling agent was added dropwise, and the reaction was heated and stirred until it became viscous to obtain a modified CaO-ZrO2 composite slurry; (1) C4H6CaO4, Z The molar ratio of rOCl2·8H2O is 1:1; the mass ratio of C4H6CaO4, ethanol aqueous solution and polyethylene glycol is 1:6:0.05; (1) the drying time is 90℃, 8h; the calcination process conditions are: temperature 700℃, time 2h; (2) the mass ratio of CaO-ZrO2 composite powder, nano-Al2O3, anhydrous ethanol and silane coupling agent is 5:0.5:15:0.05; (2) the process conditions of heating and stirring reaction are: temperature 65℃, stirring speed 80r / min; the process conditions of ultrasonic dispersion are: frequency 20kHz, time 3min; 3. Preparation process of high-strength and high-temperature resistant alloy strip: S1: Melting and forming the alloy to obtain a slab; S2: Grinding and finishing the slab in S1, hot rolling, bright annealing, and grinding and finishing again to obtain a semi-finished alloy strip; S3: Cold rolling and annealing the semi-finished alloy strip in S2, cold rolling and annealing again, and then inspecting and trimming to obtain a finished alloy strip; S4: Ultrasonic cleaning and drying the finished alloy strip in S3, spraying modified Al-Si slurry on the surface of the finished alloy strip, curing to form a metal bonding layer, and then coating the surface of the metal bonding layer with modified CaO-ZrO2 composite slurry, curing to form a thermal barrier coating, and obtaining a high-strength and high-temperature resistant alloy strip; the melting and forming temperature in S1 is 1400°C; the hot rolling temperature in S2 is 1100°C; the bright annealing in S2 is carried out in a bright annealing furnace protected by pure hydrogen, and the process conditions are: temperature 1100°C, time 5min, hydrogen spraying volume 35m 3 / h; the process conditions for cold rolling in S3 are: temperature 400℃, time 0.5h; the process conditions for annealing are: temperature 1100℃, time 50min; the process conditions for ultrasonic cleaning in S4 are: frequency 20Hz, time 0.5h; the process conditions for spraying in S4 are: spray volume 5mL / min, nozzle pressure 2KPa; the process conditions for curing in S4 are: temperature 900℃, time 1h; the thickness of the metal bonding layer in S4 is 0.3mm; the thickness of the thermal barrier coating in S4 is 0.5mm.
[0033] Embodiment 2: A process for preparing a high-strength, high-temperature-resistant alloy strip for a hot end component, comprising the following steps: 1. Preparation of modified Al-Si slurry: Step 1: Mix nano-La2O3 and NaCl solution in a mass ratio of 2:6, and ultrasonicate to obtain La2O3 slurry; Step 2: Mix Al powder, Si powder, Al2O3 powder with the La2O3 slurry in step 1, add silane coupling agent, stir evenly, and obtain modified Al-Si slurry; in step 2, the mass ratio of Al powder, Si powder, Al2O3 powder, La2O3 slurry, and silane coupling agent is 1.5:0.7:5:11:0.07; 2. Preparation of modified CaO-ZrO2 composite slurry: (1) C4H6CaO4, ZrOCl2·8H2O and 80% ethanol aqueous solution were mixed, polyethylene glycol was added, stirred evenly, the pH was adjusted to 10, stirred evenly, ultrasonically dispersed, and the obtained mixed solution was heated to 60°C in a water bath to form a gel, dried and ground, and calcined to obtain CaO-ZrO2 composite powder; (2) CaO-ZrO2 composite powder, nano-Al2O3 and anhydrous ethanol were mixed, ultrasonically dispersed, silane coupling agent was added dropwise, and the reaction was heated and stirred until it became viscous to obtain modified CaO-ZrO2 composite slurry; (1) C4H6CaO4 and ZrO The molar ratio of Cl2·8H2O is 2:2; the mass ratio of C4H6CaO4, ethanol aqueous solution and polyethylene glycol is 1:8:0.07; (1) the drying time is 100℃, 10h; the calcination process conditions are: temperature 900℃, time 2-4h; (2) the mass ratio of CaO-ZrO2 composite powder, nano-Al2O3, anhydrous ethanol and silane coupling agent is 7:0.07:20:0.07; (2) the heating and stirring reaction process conditions are: temperature 75℃, stirring speed 90r / min; the ultrasonic dispersion process conditions are: frequency 30kHz, time 4min; 3. Preparation process of high-strength and high-temperature resistant alloy strip: S1: Melting and forming the alloy to obtain a slab; S2: Grinding and finishing the slab in S1, hot rolling, bright annealing, and grinding and finishing again to obtain a semi-finished alloy strip; S3: Cold rolling and annealing the semi-finished alloy strip in S2, cold rolling and annealing again, and then inspecting and trimming to obtain a finished alloy strip; S4: Ultrasonic cleaning and drying the finished alloy strip in S3, spraying modified Al-Si slurry on the surface of the finished alloy strip, curing to form a metal bonding layer, and then coating the surface of the metal bonding layer with modified CaO-ZrO2 composite slurry, curing to form a thermal barrier coating, and obtaining a high-strength and high-temperature resistant alloy strip; the melting and forming temperature in S1 is 1500℃; the hot rolling temperature in S2 is 1200℃; the bright annealing in S2 is carried out in a bright annealing furnace protected by pure hydrogen, and the process conditions are: temperature 1200℃, time 10min, hydrogen spraying amount 45m 3 / h; the process conditions for cold rolling in S3 are: temperature 500℃, time 1h; the process conditions for annealing are: temperature 1200℃, time 70min; the process conditions for ultrasonic cleaning in S4 are: frequency 30Hz, time 1h; the process conditions for spraying in S4 are: spray volume 10mL / min, nozzle pressure 6KPa; the process conditions for curing in S4 are: temperature 1000℃, time 2h; the thickness of the metal bonding layer in S4 is 0.5mm; the thickness of the thermal barrier coating in S4 is 0.7mm.
[0034] Embodiment 3: A process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component, comprising the following steps: 1. Preparation of modified Al-Si slurry: Step 1: Mix nano-La2O3 and NaCl solution in a mass ratio of 3:8, and ultrasonicate to obtain La2O3 slurry; Step 2: Mix Al powder, Si powder, Al2O3 powder with the La2O3 slurry in step 1, add silane coupling agent, and stir evenly to obtain modified Al-Si slurry; in step 2, the mass ratio of Al powder, Si powder, Al2O3 powder, La2O3 slurry, and silane coupling agent is 2:1:6:15:0.1; 2. Preparation of modified CaO-ZrO2 composite slurry: (1) C4H6CaO4, ZrOCl2·8H2O and 80% ethanol aqueous solution were mixed, polyethylene glycol was added, stirred evenly, the pH was adjusted to 11, stirred evenly, ultrasonically dispersed, and the obtained mixed solution was heated to 70°C in a water bath to form a gel, dried and ground, and calcined to obtain CaO-ZrO2 composite powder; (2) CaO-ZrO2 composite powder, nano-Al2O3 and anhydrous ethanol were mixed, ultrasonically dispersed, silane coupling agent was added dropwise, and the reaction was heated and stirred until it became viscous to obtain a modified CaO-ZrO2 composite slurry; (1) C4H6CaO4, Z The molar ratio of rOCl2·8H2O is 3:3; the mass ratio of C4H6CaO4, ethanol aqueous solution and polyethylene glycol is 1:10:0.1; (1) the drying time is 110℃, 12h; the calcination process conditions are: temperature 1100℃, time 4h; (2) the mass ratio of CaO-ZrO2 composite powder, nano-Al2O3, anhydrous ethanol and silane coupling agent is 10:1:25:0.1; (2) the process conditions of heating and stirring reaction are: temperature 85℃, stirring speed 100r / min; the process conditions of ultrasonic dispersion are: frequency 40kHz, time 5min; 3. Preparation process of high-strength and high-temperature resistant alloy strip: S1: Melting and forming the alloy to obtain a slab; S2: Grinding and finishing the slab in S1, hot rolling, bright annealing, and grinding and finishing again to obtain a semi-finished alloy strip; S3: Cold rolling and annealing the semi-finished alloy strip in S2, cold rolling and annealing again, and then inspecting and trimming to obtain a finished alloy strip; S4: Ultrasonic cleaning and drying the finished alloy strip in S3, spraying modified Al-Si slurry on the surface of the finished alloy strip, curing to form a metal bonding layer, and then coating the surface of the metal bonding layer with modified CaO-ZrO2 composite slurry, curing to form a thermal barrier coating, and obtaining a high-strength and high-temperature resistant alloy strip; the melting and forming temperature in S1 is 1600°C; the hot rolling temperature in S2 is 1300°C; the bright annealing in S2 is carried out in a bright annealing furnace protected by pure hydrogen, and the process conditions are: temperature 1300°C, time 15min, hydrogen spraying amount 55m 3 / h; the process conditions for cold rolling in S3 are: temperature 600℃, time 1.5h; the process conditions for annealing are: temperature 1300℃, time 90min; the process conditions for ultrasonic cleaning in S4 are: frequency 40Hz, time 1.5h; the process conditions for spraying in S4 are: spray volume 15mL / min, nozzle pressure 10KPa; the process conditions for curing in S4 are: temperature 1100℃, time 3h; the thickness of the metal bonding layer in S4 is 0.8mm; the thickness of the thermal barrier coating in S4 is 1mm.
[0035] Comparative Example 1: Using Example 1 as a comparison, the Al-Si slurry was not modified and other conditions remained unchanged.
[0036] Comparative Example 2: Taking Example 1 as a comparison, the CaO-ZrO2 composite powder is not coated and modified, and the other conditions remain unchanged.
[0037] Comparative Example 3: Compared with Example 1, neither the Al-Si slurry is modified nor the CaO-ZrO2 composite powder is coated and modified, and the other conditions remain unchanged.
[0038] Experiment: Take the alloy strips obtained in Examples 1 to 3 and Comparative Examples 1 to 3, prepare samples, test their properties respectively and record the test results: Tensile property test: The alloy strips obtained in Examples 1-3 and Comparative Examples 1-3 were subjected to tensile property tests at room temperature and 1000° C., respectively; Corrosion resistance test: Acid etching solution was prepared according to the method of ISO10271, and the alloy strips obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were placed in the acid etching solution for 200 hours, and the surface cracks were observed; The following table shows the test results of tensile strength and corrosion resistance of the alloy strip;
[0039] According to the data in the above table, we can draw the following conclusions: The alloy strips obtained in Examples 1-3 are compared with the alloy strips obtained in Comparative Examples 1-3. The test results show that: Compared with Example 1, Comparative Example 1 does not modify the Al-Si slurry, and its tensile strength and corrosion resistance are reduced. This is because nano-La2O3 has good corrosion resistance. After removing nano-La2O3, the corrosion resistance of the coating is reduced. Compared with Example 1, the tensile strength of Comparative Example 2, which does not coat and modify the CaO-ZrO2 composite powder, is reduced because the nano-Al2O3 coating modification can improve the dispersibility of the powder in the slurry, making the coating more uniform and dense, and improving the mechanical properties and high temperature resistance of the thermal barrier coating; Compared with Example 1, Comparative Example 3 neither modified the Al-Si slurry nor coated the CaO-ZrO2 composite powder, and its tensile strength and corrosion resistance decreased significantly; It can be seen that the setting of the process and the materials used in this application can promote the improvement of the high temperature resistance, tensile strength and corrosion resistance of the alloy strip.
[0040] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A high-strength, high-temperature-resistant alloy strip for hot end components, characterized in that: Includes alloy strips, metal bond coats and thermal barrier coatings; The alloy strip comprises the following mass components: Al: 10.5-20.5%, Cr: 5.5-10.5%, Mo: 8.0-12.0%, Fe: 14.5-20.5%, and the balance is Ni; The metal bonding layer comprises the following components: nano La2O3, Al powder, Si powder, Al2O3 powder; The thermal barrier coating comprises the following components: CaO, ZrO2, nano-Al2O3.
2. A process for preparing a high-strength, high-temperature-resistant alloy strip for hot end components, characterized in that: The following steps are involved: S1: Melting the alloy into a slab; S2: grinding and finishing the slab described in S1, hot rolling, bright annealing, and grinding and finishing again to obtain a semi-finished alloy strip; S3: cold rolling, annealing, cold rolling again, annealing, and then inspecting and trimming the semi-finished alloy strip in S2 to obtain a finished alloy strip; S4: ultrasonically clean and dry the finished alloy strip described in S3, spray modified Al-Si slurry on the surface of the finished alloy strip, solidify it to form a metal bonding layer, and then coat the surface of the metal bonding layer with modified CaO-ZrO2 composite slurry, solidify it to form a thermal barrier coating, and obtain a high-strength and high-temperature resistant alloy strip.
3. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 2, characterized in that: The hot rolling temperature in S2 is 1100-1300°C; Bright annealing in S2 is carried out in a bright annealing furnace protected by pure hydrogen. The process conditions are: temperature 1100-1300℃, time 5-15min, hydrogen injection volume 35-55m 3 / h.
4. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 2, characterized in that: The process conditions of ultrasonic cleaning in S4 are: frequency 20-40 Hz, time 0.5-1.5 h; The process conditions of spraying in S4 are: spray volume 5-15mL / min, nozzle pressure 2-10KPa; The curing process conditions in S4 are: temperature 900-1100°C, time 1-3h.
5. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 2, characterized in that: The modified Al-Si slurry is prepared by the following process: Step 1: Mix nano-La2O3 with NaCl solution and perform ultrasonic treatment to obtain La2O3 slurry; Step 2: Mix Al powder, Si powder, Al2O3 powder and the La2O3 slurry in step 1, add silane coupling agent, stir evenly, and obtain modified Al-Si slurry.
6. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 2, characterized in that: The modified CaO-ZrO2 composite slurry is prepared by the following process: (1) C4H6CaO4, ZrOCl2·8H2O and ethanol aqueous solution are mixed, polyethylene glycol is added, stirred evenly, the pH is adjusted to 9-11, stirred evenly, ultrasonically dispersed, and the obtained mixed solution is heated in a water bath to 50-70°C to form a gel, dried, ground, and calcined to obtain CaO-ZrO2 composite powder; (2) Mix the CaO-ZrO2 composite powder, nano-Al2O3 and anhydrous ethanol, disperse them by ultrasonication, add a silane coupling agent dropwise, heat and stir to react until it becomes viscous, and obtain a modified CaO-ZrO2 composite slurry.
7. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 5, characterized in that: In step 1, the mass ratio of nano-La2O3 and NaCl solution is (1-3): (5-8); In step 2, the mass ratio of Al powder, Si powder, Al2O3 powder, La2O3 slurry and silane coupling agent is (1-2): (0.5-1): (4-6): (8-15): (0.05-0.1).
8. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 6, characterized in that: (1) The molar ratio of C4H6CaO4 and ZrOCl2·8H2O is (1-3): (1-3); (1) The mass ratio of C4H6CaO4, ethanol aqueous solution and polyethylene glycol is 1: (6-10): (0.05-0.1).
9. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 5, characterized in that: (1) The drying time is 8-12 hours at 90-110°C; (1) The calcination process conditions are: temperature 700-1100°C, time 2-4h.
10. The process for preparing a high-strength and high-temperature-resistant alloy strip for a hot end component according to claim 5, characterized in that: (2) The mass ratio of CaO-ZrO2 composite powder, nano-Al2O3, anhydrous ethanol and silane coupling agent is (5-10): (0.5-1): (15-25): (0.05-0.1).